Fighting with the Longsword: Modern-day HEMA Practices - Gassmann Jack; Gassmann Jürg; Le Coultre Dominique (Acta Periodica Duellatorum)
This article is based on the talk presented on 27th November 2016 in the course of the Journées d’études sur le costume et les simulateurs d’armes dans les pratiques d’arts martiaux anciens. The talk itself involved practical demonstrations and interaction with other presentations given at the event; this article does not purport to be a transcript of the presentation, but elaborates on the key themes of the presentation: The objectives of HEMA as a modern practice, and their relationship to what we know about the historical practice of the European martial arts in the Middle Ages, including physical fitness, fencing techniques and tactical awareness, based on the Fechtbücher extant. A key element of the discussion involved a comparison between the objectives of and drivers behind historical and modern tournament rule-sets.